1996
DOI: 10.1177/000992289603500204
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Sequelae of Pneumococcal Meningitis in Children

Abstract: The purpose of this study was to assess the long-term effects of pneumococcal meningitis in children. From 1967 to 1988, a total of 90 children were admitted to the Hospital for Infectious Diseases, Thessaloniki, Greece, with the diagnosis of pneumococcal meningitis. Sixteen patients died in the hospital as a direct result of meningitis. Eleven others were excluded from the study (neurologic deficits prior to onset of meningitis, two; death subsequent to hospitalization, two; recurrent meningitis, seven). Of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(31 citation statements)
references
References 26 publications
2
28
0
1
Order By: Relevance
“…However, the proportion of patients reporting partial or profound hearing loss in our study (26%) is highly comparable with estimates from other studies [23] that suggest 30% [2] of children and 22% of adults [31] have hearing loss after PM.…”
Section: Strengths and Limitationssupporting
confidence: 90%
“…However, the proportion of patients reporting partial or profound hearing loss in our study (26%) is highly comparable with estimates from other studies [23] that suggest 30% [2] of children and 22% of adults [31] have hearing loss after PM.…”
Section: Strengths and Limitationssupporting
confidence: 90%
“…The literature search identified 15 cases in which the authors suggested that a chronic parameningeal focus had been the source of recurrent episodes of meningitis (11,56,78,102,124,127,161,167,169,215). This group comprised 11 cases of chronic otitis media and/or mastoiditis, two cases of chronic sinusitis (sphenoidal and maxillary), and two cases of chronic osteomyelitis of the skull (Table 3).…”
Section: Chronic Parameningeal Infectionsmentioning
confidence: 99%
“…The corresponding estimate in this paper using only studies on patients recruited after 1990 is 23.9%, 6.2% and 9.4%. Mental retardation, a further category reported by Baraff and co-workers, was not extracted because only two studies reported such a diagnosis, and the two studies used imprecise but non-equivalent descriptions ("severe mental retardation" 25 and "mental retardation" 24 ).…”
Section: Discussionmentioning
confidence: 99%